2004
DOI: 10.1002/app.13566
|View full text |Cite
|
Sign up to set email alerts
|

Experimental verification of failure of Amontons' law in polymeric textiles

Abstract: ABSTRACT:The dynamic friction of a variety of textile materials was studied and was experimentally proven that the frictional behavior of textile materials do not obey the Amontons' basic law of friction (F/N ϭ ). Both woven and nonwoven materials with different fiber content and constructional features were used in the study. Results show that the dynamic friction-normal load relationship is not a straight line passing through origin. A statistical approach has been followed to prove the significance of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…This can be attributed to greater deformation and compression of the hairy fabric structure, accompanied by an increase in the real contact area. This frictional behaviour is consistent with several previous investigations (22,63). Other authors found that the COF declined with increasing load (20,24,59).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This can be attributed to greater deformation and compression of the hairy fabric structure, accompanied by an increase in the real contact area. This frictional behaviour is consistent with several previous investigations (22,63). Other authors found that the COF declined with increasing load (20,24,59).…”
Section: Discussionsupporting
confidence: 94%
“…In this study, the majority of the friction experiments were carried out at a constant normal load and sliding velocity. Previous studies have conclusively shown that friction coefficients depend on pressure (20, 22, 24, 26, 59) and sliding velocity (10, 16, 19) due to the viscoelastic, strain‐dependent properties of polymeric textile structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the viscoelastic deformation occurs, the relationship between the normal load and friction will accord with the power-law. Ramkumar et al [4] studied the dynamic friction of a variety of textile materials and verified that the frictional behavior of textile materials do not obey the Amonton's basic law of friction. Ajayi and Elder [5][6][7] also considered that the friction of textile fiber, yarn and fabric does not obey the Amonton's law which only fits with pure rigidity body.…”
Section: Introductionmentioning
confidence: 98%
“…However, some authors claim that this relation does not hold for dynamic situations for polymeric (woven) textiles (Ramkumar et al, 2004) and that…”
Section: Resultsmentioning
confidence: 99%